OTA-based capacitance-to-period converter for capacitive sensors - Kanjanapart, Naratorn; Cheypoca, Thepjit; Riewruja, Vanchai; Petchmaneelumka, Wandee (My University, 2013)
A simple design technique for realization of a capacitance-to-period converter based on operational transconductance amplifiers (OTAs) is presented in this paper. The proposed principle utilizes the behavior of astable multivibrator. The configuration of converter is implemented using commercial available and low cost devices. The obtained time period is proportional to sensing capacitance. The conversion gain of proposed scheme can be changed by electronic means. Circuit performances verified by experimental results are agreed with the expected values. © 2013 ICIC International.
Keywords: Capacitance-to-period converter; Capacitive sensor; Interface circuit; OTA